A comparison between cytology and histology to detect anal intraepithelial neoplasia. Issue 1 (February 1994) - de Ruiter, A; Carter, P; Katz, D R; Kocjan, G; Whatrup, C; Northover, J; Mindel, A
Abstract : INTRODUCTION--Anal intraepithelial neoplasia (AIN), which may be a precursor of anal carcinoma, has been identified on histology following minor anal surgical procedures, in particular the removal of perianal condylomata, in increasing numbers of homosexual and bisexual men. Anal cytology has recently been proposed as a useful method of identifying AIN lesions. OBJECTIVE--To compare anal cytology with histology as a method of detecting AIN. METHODS--215 homosexual and bisexual men attending a central London sexually transmitted diseases clinic had an anal cytological smear performed under standard conditions. The perianal area and anal canal were then examined using a colposcope, and areas macroscopically suggestive of intraepithelial neoplasia were biopsied. RESULTS--176 of the 215 patients were biopsied of whom 76 had AIN on histology. 154 of the 215 patients had an adequate anal smear of whom 46 and 85 had cytological features of both HPV and AIN, or HPV alone respectively. Including features of HPV alone as an abnormal smear, anal cytology, when compared with anoscopy and histology as the gold standard for diagnosing AIN, resulted in a sensitivity of 87.5%, a specificity of 16.3%, a positive predictive value of 37.4% and a negative predictive value of 69.6%. Restricting abnormal smears to those with features of both HPV and AIN resulted in a sensitivity of 33.9%, a specificity of 72.5%, a positive predictive value of 41.3% and a negative predictive value of 65.7%. CONCLUSION--Anal cytology is a sensitive but nonspecific method of identifying patients with biopsy proven AIN if cytological features of HPV alone are included as abnormal smears. Specificity is improved by restricting abnormal smears to those with features of both HPV and AIN but this markedly lowers the sensitivity of the test. At present, anoscopy and histology are required in addition to anal cytology to differentiate between patients who simply have anal condylomata and those who also have AIN.